Theoretical And Empirical Studies Of The Use Of Problem Base Learning In The Technical And Vocational Education And Training (TVET) In The Context Of The XXI Century (Indonesian Journal of Learning Education and Counseling, 2019)
The research aims to find out: (1) how far PBL has been used as a learning model in the vocational environment; and (2) how far is the influence of PBL on learning outcomes? The study was conducted with literature studies through theoretical and empirical studies of references and relevant research results, and continued with focus group discussions (FGD). The relevant references include learning theories, and theories about problem base learning (PBL). While the study of the results of relevant research, is a study of studies on the influence of PBL on "learning out comes" in vocational high school students as an integral part of technical, vocational, education and training (TVET). The study concluded that: (1) PBL has been widely used in learning in the vocational environment; (2) PBL is able to improve student learning achievement both process and results; and (3) the number of students who actively study, the number of students who ask questions, and student learning outcomes increase significantly on the application of PBL.